Colocalization of Tectal Inputs With Amygdala-Projecting Neurons in the Macaque Pulvinar - Elorette, Catherine; Forcelli, Patrick A.; Saunders, Richard C.; Malkova, Ludise (Frontiers in Neural Circuits, 2018)
Neuropsychological and neuroimaging studies have suggested the presence of a fast, subcortical route for the processing of emotionally-salient visual information in the primate brain. This putative pathway consists of the superior colliculus, pulvinar, and amygdala. While the presence of such a pathway has been confirmed in sub-primate species, it has yet to be documented in the primate brain using conventional anatomical methods. We injected retrograde tracers into the amygdala and anterograde tracers into the colliculus, and examined regions of co-localization of these signals within the pulvinar of the macaque. Anterograde tracers injected into the superior colliculus labeled axonal projections within the pulvinar, primarily within the oral, lateral, and medial subdivisions. These axonal projections from the colliculus co-localized with cell bodies within the pulvinar that were labeled by retrograde tracer injected into the lateral amygdala. This zone of overlap was most notable in the medial portions of the medial, oral and inferior pulvinar, and was often densely concentrated in the vicinity of the brachium of the superior colliculus. These data provide an anatomical basis for the previously suggested pathway mediating fast processing of emotionally salient information.